Contract or Disobedience?: Reframing Azoulay. (4th May 2017) - Fardy, Jonathan
Abstract : The Civil Contract of Photography by Ariella Azoulay has profoundly reshaped the critical study of photography. The concept of "the civil concept of photography" is as intriguing as it is ill-defined. This essay seeks to clarify it. It begins by situating Azoulay's theory in the single context that has most dramatically stamped her thinking — Palestine. It is in her thinking through photography and the Palestinian question that her debt to, and divergence from, the tradition of social contract theory is clearly seen. It concludes that Azoulay's central concept — "the civil contract of photography" — is better understood when seen from the combined perspective of Schmitt's theory of decision and Thoreau's concept of civil disobedience.